Thermogravimetric Method for Accurate Determination of Thermodynamic Quantities at High Temperatures - Harbbi, K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This researd exhibit's a method to  determine the change in Gibbs function,(enthai py,entropy.     and     specific     heat     capacity)      tor monovariant   heterogeneous   equilibria   .The  thermodynamical quan.tities were obtained jndirectly with m the measurment  of temperature dependent on eql,lilibrium system.